Religious giving in Romania (Economic and Political Thought, 2016)
The paper analyzes the practice of religious giving in Romania. In the firstpart the authors examine the recent scientific literature regarding the predictorsof religious giving. Secondly, they quantitatively explore a data base ofreligious behavior corresponding to a Romanian national sample from 2011using the R statistical software. Interpretation of the obtained results andconclusions are presented in the last part of the study.